Theoretical Analysis of the Effect of Cesium Impuritieson the Copper-Vapor Laser Performance; Laser Physics; Vol. 14, No. 6 - Boichenko A. M.; Evtushenko G. S. Gennady Sergeevich; Yakovlenko S. I.; Zhdaneev O. V. (2004, 2004)
A nonstationary kinetic model of the active medium of a copper-vapor laser ( = 510 and 578 nm) with cesium impurities is constructed. An analysis of the existing experimental and theoretical concepts regard-ing the increase in the lasing parameters of a copper-vapor laser with cesium impurities in the active medium is presented. The reasons for the increase in these parameters are elucidated. Data regarding the increase in the lasing efficiency and power in the presence of the optimum cesium impurities are obtained.